Alpha 2 agonist dexmedetomidine as an adjuvant to bupivacaine in supraclavicular brachial plexus block - Waindeskar, Vaishali; Jain, Abhilekh; Kumar, Jitendra; Pandey, Anupam; Songir, Sheetal (International Journal of Medical Research and Review, 2016)
Background: Regional anesthesia is a recommended technique for upper limb surgeries with better postoperative profile. Alpha-2 agonists are added to local anesthetic agents to extend the duration of nerve blocks. We evaluated the effect of combining dexmedetomidine with bupivacaine with respect to duration of motor and sensory block and duration of analgesia. Materials and Methods: Sixty patients posted for upper limb surgeries were enrolled for a prospective, randomized, study. Patients were divided into two groups, the control group B and the study group BD. In group B (n = 30), 30 ml of 0.325% bupivacaine + normal saline; and in group BD (n = 30), 30 ml of 0.325% bupivacaine +1μg/kg dexmedetomidine given ultrasound guided supraclavicular brachial plexus block. Results: The onset times for sensory and motor blocks were significantly shorter in BD than B group (p < 0.05), while the duration of sensory and motor blocks was significantly longer in BD group. The duration of analgesia was significantly longer in BD group than B group (p < 0.0001). SBP and DBP levels in BD group were significantly lower than in B group 20 min after block (p < 0.001). Bradycardia was observed in two patients in the group BD. Conclusion: Dexmedetomidine added as an adjuvant to bupivacaine for supraclavicular brachial plexus block significantly shortens the onset time and prolongs the duration of sensory and motor blocks and duration of analgesia. Patients in group BD were adequately sedated with no adverse effects except bradycardia in two patients.